Microbiological Examination of Imported Cosmetic Products in the Kurdistan/Iraq Market: A Comprehensive Analysis - Yousif Hamed Mohamed-sharif; Bizhar Ahmed Tayeb; Farhad Ramadhan Choli; Hivi Salim Khamo; Mohammed Mahmood Ibrahim (Viva Medika, 2024)
The presence of diverse nutrient levels in cosmetics can facilitate microbial proliferation. Typically, bacteria such as Staphylococcus, Pseudomonas, and Klebsiella spp. are implicated in the contamination of cosmetic products. It is highly plausible that the microorganisms identified in cosmetic items emanate from contaminated water sources. The primary aim of this study was to perform a comprehensive microbial analysis of specific brands of cosmetics frequently utilized in Iraqi communities. The scrutinized products encompassed a range of items, including hair shampoo, hair conditioner, skin cream, wet wipes, toothpaste, liquid soap, and baby shampoo. Within the scope of this investigation, 84 cosmetic products were examined, revealing a contamination rate of 7.14%. Predominantly, bacterial contamination was identified, with an absence of fungal contamination. Notably, hair shampoo exhibited the highest level of contamination among the examined products categories. The recovery of total viable bacterial counts was observed across all contaminated samples, including coliforms, Staphylococcus, and Pseudomonas sp. The findings of the microbial investigation indicate an elevated concentration of total viable microorganisms in all samples. Consequently, these compromised products pose substantial health risks to consumers